High speed e-beam lithography for gold nanoarray fabrication and use in nanotechnology - Trasobares, Jorge; Vaurette, François; François, Marc; Romijn, Hans; Codron, Jean-Louis; Vuillaume, Dominique; Théron, Didier; Clément, Nicolas (Beilstein Journal of Nanotechnology, 2014)
E-beam lithography has been used for reliable and versatile fabrication of sub-15 nm single-crystal gold nanoarrays and led to convincing applications in nanotechnology. However, so far this technique was either too slow for centimeter to wafer-scale writing or fast enough with the so-called dot on the fly (DOTF) technique but not optimized for sub-15 nm dots dimension. This prevents use of this technology for some applications and characterization techniques. Here, we show that the DOTF technique can be used without degradation in dots dimension. In addition, we propose two other techniques. The first one is an advanced conventional technique that goes five times faster than the conventional one. The second one relies on sequences defined before writing which enable versatility in e-beam patterns compared to the DOTF technique with same writing speed. By comparing the four different techniques, we evidence the limiting parameters for the writing speed. Wafer-scale fabrication of such arrays with 50 nm pitch allowed XPS analysis of a ferrocenylalkyl thiol self-assembled monolayer coated gold nanoarray.
Keywords: gold nanodot; gold nanoparticle; high-speed e-beam lithography; molecular electronics; nanoarray; self-assembled monolayers; XPS